Measurement of τL using the B0s→ J/ψη decay mode - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (The European physical journal. C, Particles and fields, 2023)
Using a proton–proton collision data sample collected by the LHCb detector and corresponding to an integrated luminosity of 5.7 fb−1, the lifetime of the light B0s mass eigenstate, τL , is measured using the B0s→ J/ψη decay mode to be τL = 1.445 ± 0.016(stat) ± 0.008(syst) ps. A combination of this result with a previous LHCb analysis using an independent dataset corresponding to 3 fb−1 of integrated luminosity gives τL = 1.452 ± 0.014 ± 0.007 ± 0.002 ps, where the first uncertainty is statistical, the second due to the uncorrelated part of the systematic uncertainty and the third due to the correlated part of the systematic uncertainty.